PKM PENDAMPINGAN PENYUSUNAN KELAYAKAN USAHA PADA KOPERASI SINAR SURYA PIMPINAN DAERAH MUHAMMADIYAH BATU - Sri Wahjuni Latifah; Ahmad Waluyajati (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Malang, 2020)
Mentoring at Business the Cooperative Sinar Surya PDM Economic Assembly Batu is conducted to assist partners in developing mini market business. PDM Batu City is planning to establish a mini market business as an extension of its existing business, which is cooperative store borrowing. The main obstacle is that the partner has not planned to develop a minimarket business. Besides, the partner does not have a blueprint in the form of study results and business operations guidelines mini market.This activity is done to help partners in solving business development problems. Some of the steps done for problem solving are: socialization of business development knowledge, then discuss with partner to identify and arrange business feasibility study. The next can be compiled a set of procedures and SOP operational activities in the form of goods and sales procedures. Next, do in house training for employees, implementation and mentoring the establishment of mini market.From the results of the business feasibility analysis of the establishment of mini market can be declared worthy to be established with a projected profit per year Rp 83,765,781, and with the rate of return of capital for two years and seven months.